1998
DOI: 10.1002/mrm.1910390619
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of oral choline supplement on the concentrations of choline metabolites in human brain

Abstract: Recent reports suggest that oral choline supplement may alter the cerebral choline/creatine (Cho/Cr) ratio and might be used to treat neurodegenerative disorders of cholinergic transmission. Using both 1H and 31P MRS, we reexamined the Cho/Cr ratio and quantified cerebral choline and its major constituents: phosphoethanolamine (PE), phosphorylcholine (PC), glycerophosphorylethanolamine (GPE), and glycerophosphorylcholine (GPC). In the four brain locations examined, no significant increases in Cho/Cr, [Cho], or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 11 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…The choline (Cho) signal on MRS is comprised of a group of components including free choline, phosphorylcholine, and phosphatidylcholine which constitute brain myelin and allow fluidity of cell membranes [41,42]. However, the complete metabolite profile contributing to the Cho signal is not certain [43].…”
Section: Mrs-based Central Nervous System Biochemical Analysismentioning
confidence: 99%
“…The choline (Cho) signal on MRS is comprised of a group of components including free choline, phosphorylcholine, and phosphatidylcholine which constitute brain myelin and allow fluidity of cell membranes [41,42]. However, the complete metabolite profile contributing to the Cho signal is not certain [43].…”
Section: Mrs-based Central Nervous System Biochemical Analysismentioning
confidence: 99%
“…59,80 The total observable Cho concentration in the human brain has been measured at 1-2 mM, with approximately 0.6 mM of PC and 1.0 mM of GPC. [81][82][83][84] Cho is required for the synthesis of both the neurotransmitter acetylcholine and the phospholipid phosphatidylcholine (Figure 3). Although acetylcholine is produced only by cholinergic neurons, phosphatidylcholine is produced in all cells as a major membrane constituent.…”
Section: Impaired Phospholipid Metabolism In Bipolar Disordermentioning
confidence: 99%
“…From MRS studies on tissues in vivo, the choline signal is primarily observed as a prominent singlet at 3.2 ppm that includes contributions from free choline, GPC and PC, and is often referred to as 'total choline' (38)(39)(40). In the present study, we obtained high resolution signals of Cho, PC and GPC at the chemical shifts 3.19, 3.21 and 3.22 ppm, respectively.…”
Section: Discussionmentioning
confidence: 66%